The Educational Transformation in Albania and an Analysis of the Teacher Role (Global Journal of Human-Social Science, 2024)
Abstract not found
Keywords: curriculum; voruniversitäre bildung; neue rolle der lehrenden; deutschunterricht; kompetenzen